2009
DOI: 10.1007/s00041-009-9086-9
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity in Time-Frequency Representations

Abstract: We consider signals and operators in finite dimension which have sparse time-frequency representations. As main result we show that an S-sparse Gabor representation in C n with respect to a random unimodular window can be recovered by Basis Pursuit with high probability provided that S ≤ Cn/ log(n). Our results are applicable to the channel estimation problem in wireless communications and they establish the usefulness of a class of measurement matrices for compressive sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…In particular, it implies the first uniform sparse recovery result with a linear scaling of the number of samples m in the sparsity s (up to log-factors). A non-uniform recovery result for Gabor synthesis matrices with Steinhaus generator (see Section 2 for the definition) appears in [32], where it was shown that a fixed s-sparse vector is recovered from its image under a random draw of the m × m 2 Gabor synthesis matrix via ℓ 1 -minimization with high probability provided that m ≥ Cs log m. Again, the conclusion of Theorem 1.3 is stronger than this previous result in the sense that it implies uniform and stable s-sparse recovery. Further related material may be found in [33,2].…”
Section: Theorem 13 Let ǫ Be a Rademacher Vector And Consider The Gamentioning
confidence: 99%
“…In particular, it implies the first uniform sparse recovery result with a linear scaling of the number of samples m in the sparsity s (up to log-factors). A non-uniform recovery result for Gabor synthesis matrices with Steinhaus generator (see Section 2 for the definition) appears in [32], where it was shown that a fixed s-sparse vector is recovered from its image under a random draw of the m × m 2 Gabor synthesis matrix via ℓ 1 -minimization with high probability provided that m ≥ Cs log m. Again, the conclusion of Theorem 1.3 is stronger than this previous result in the sense that it implies uniform and stable s-sparse recovery. Further related material may be found in [33,2].…”
Section: Theorem 13 Let ǫ Be a Rademacher Vector And Consider The Gamentioning
confidence: 99%
“…The matrix Ψ g ∈ C n×n 2 whose columns list the members π(λ)g, λ ∈ Z n ×Z n , of the Gabor system is referred to as Gabor synthesis matrix [16,32,40]. Note that Ψ g allows for fast matrix vector multiplication algorithms based on the FFT.…”
Section: Time-frequency Structured Measurement Matricesmentioning
confidence: 99%
“…A large body of literature extends these results to measurements of signals in the presence of noise, to signals that are not exactly sparse but compressible, 5 to several types of measurement matrices 6,[21][22][23]27 and to measurement models beyond simple sparsity. 2 …”
Section: Compressed Sensing Backgroundmentioning
confidence: 99%